Dampak Pemekaran Daerah Kabupaten/ Kota - Iskatrinah; Doni Adi Supriyo (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2021)
The availability of regulatory opportunities for the expansion of autonomous regions, or the formation of newautonomous regions, is actually not a new thing in the history of regional government in Indonesia. Since thecentralized system of government during the New Order era, the government has also done a lot of establishingnew autonomous regions. In the 1945 Constitution of the Republic of Indonesia, the territory of the Unitary Stateof the Republic of Indonesia is divided into provincial areas and provincial areas are divided into regencies/cities,each of which has a regional government to carry out regional autonomy as widely as possible. Regionalautonomy is the right, authority, and obligation of an autonomous region to regulate and manage its owngovernment affairs and the interests of the local community in accordance with statutory regulations. Thepurpose of this study is to find out more about the impact of the division of districts/cities in a decentralizedunitary state. The research method used in this research is using normative legal research methods, with theresult that the ability of the regions to exercise authority after the division is not the same because each hasdifferent conditions and characteristics. Regional expansion has an impact on culture, public services, economicdevelopment, defense, security and national integration. The formation of regions through the division ofregency/municipal regions in reality cannot be the main choice in accelerating development. But on the otherhand, regional formation is also not something to be avoided. The conclusion of this study is that the formation ofregions through the division of regencies/municipalities is actually a difficult thing, but the trend of expansioncontinues to increase, in fact regional expansion cannot be the main choice in accelerating development. But onthe other hand, regional formation is also not something to be avoided